Barriers and enablers for iron folic acid (IFA) supplementation in pregnant women - Siekmans, Kendra (Matern Child Nutr, 2017)
In order to inform large scale supplementation programme design, we review and summarize the barriers and enablers for improved coverage and utilization of iron and folic acid (IFA) supplements by pregnant women in 7 countries in Africa and Asia. Mixed methods were used to analyse IFA supplementation programmes in Afghanistan, Bangladesh, Indonesia, Ethiopia, Kenya, Nigeria, and Senegal based on formative research conducted in 2012–2013. Qualitative data from focus‐group discussions and interviews with women and service providers were used for content analysis to elicit common themes on barriers and enablers at internal, external, and relational levels. Anaemia symptoms in pregnancy are well known among women and health care providers in all countries, yet many women do not feel personally at risk. Broad awareness and increased coverage of facility‐based antenatal care (ANC) make it an efficient delivery channel for IFA; however, first trimester access to IFA is hindered by beliefs about when to first attend ANC and preferences for disclosing pregnancy status. Variable access and poor quality ANC services, including insufficient IFA supplies and inadequate counselling to encourage consumption, are barriers to both coverage and adherence. Community‐based delivery of IFA and referral to ANC provides earlier and more frequent access and opportunities for follow‐up. Improving ANC access and quality is needed to facilitate IFA supplementation during pregnancy. Community‐based delivery and counselling can address problems of timely and continuous access to supplements. Renewed investment in training for service providers and effective behaviour change designs are urgently needed to achieve the desired impact.